Peran Lipat Tiga (Triple Roles) Perempuan Lanjut Usia Pengrajin Anyaman Pandan di Desa Mbatakapidu - Soni Rambe Pero; Rambu L. K. R. Nugrohowardhani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study is to understand the triple roles of elderly women who are still productive in the pandan leaf weaving business in Mbatakapidu Village, Waingapu City District, East Sumba Regency, through a description of: Reproductive Roles, Production Roles and Social/Community Roles. This study attempts to understand the role of elderly women weaving craftsmen through the lens of the triple roles theory. By utilizing qualitative research methods and data collection techniques are interviews, observation and documentation. Data analysis techniques include data reduction, data presentation and drawing conclusions. The results of this study indicate that the elderly in Mbatakapidu Village are still productive in doing household chores and weaving, this is done to fulfill household life. Age is no longer an obstacle for elderly women weaving craftsmen in Mbatakapidu because they are still able to carry out three-fold roles, namely the role of reproduction, the role of production and social roles, only to fulfill household needs or household economics. While elderly women should be able to no longer work and focus on their health due to their susceptibility to illness, the opposite is true in Mbatakapidu. This triple role is truly implemented by the elderly women through mat weaving.